Ethics and experience : moral theory from just war to abortion - Steffen, Lloyd H., 1951- (Lanham : Rowman & Littlefield Publishers, 2012)
Ethics and Experience introduces students to the key topics in moral theory through provocative moral issues-just war, abortion, physician assisted suicide, the death penalty and more. Steffen helps students bridge the gap between ethical theory and experience through developing a "common agreement" ethical system that is applicable to a variety of moral problems and issues with clear language and real-life examples.
Part I: Ethics -- Just War as an Ethic -- Nonviolent Resistance as a Use of Force -- The Hybrid Ethic and Its Application -- Using the Common Agreement Ethic -- Part II: Experience -- The Ethics of Physician-Assisted Suicide -- The Ethics of Patient Nontreatment -- The Ethics of Execution and Just Punishment -- The Ethics of Abortion -- The Ethics of War.
Includes bibliographical references and index.
Print version record.
English.
Master record variable field(s) change: 650
Keywords: Ethics; Euthanasia; Medical ethics; Capital punishment; Abortion; Just war doctrine; PHILOSOPHY -- Ethics & Moral Philosophy; PHILOSOPHY -- Social; Ethics; Electronic books